Improving Thematic Learning Outcomes on Number Place Value using the Demonstration Method and Glass Media - Meda Aldila; R. Hariyani Susanti (Universitas Negeri Padang, 2022)
This research is motivated by the poor learning outcomes of the first-grade students at SDN Grogol Utara 09. So far, in learning Mathematics, teachers only emphasize cognitive aspects. Where the teacher explains a lot of material and gives questions to students without paying attention to how well students understand the subject. This in turns push the students to get bored quickly and are not enthusiastic about learning. As a result, interest and learning outcomes in mathematics decrease. The purpose of this study was to find out whether student learning outcomes have increased in terms of place value in numbers using the demonstration method and glass media in grade 1 students at SDN Grogol Utara 09. This research was conducted in two cycles on the material place value in numbers. Based on the results of the improvement, it turned out that it was able to increase the achievement of grade 1 students at SDN Grogol Utara in Mathematics. It was proven by obtaining the class average scores in the 1st cycle improvement, namely 62.5 and 79.5 in the 2nd cycle improvement. It was stated that there was an increase of 17 points. Thus, the use of the Demonstration method with glass media in learning Mathematics about determining place value in numbers turns out to be able to improve grade 1 student achievement at SDN Grogol Utara 09 in Mathematics